“Keep It Within the Family”: Legal Intervention in the Social Normalization of Domestic Violence in Indonesian Communities - Muhammad Iqbal Baiquni; Septhian Eka Adiyatma (JUSTISIA GLOBAL EDUKASI, 2026)
Domestic violence in Indonesia is not merely a private family matter but a social problem shaped by cultural expectations, gender relations, economic dependency, and community attitudes. The persistent perception that domestic violence should be resolved within the family may discourage victims from seeking formal legal protection and encourage informal reconciliation even in serious cases. This article examines the limitations and challenges of legal intervention in addressing the social normalization of domestic violence within Indonesian communities. Employing a socio-legal approach, the study analyzes the relationship between the domestic violence legal framework, community-based dispute resolution, family intervention, and victims' access to justice. The study argues that the existence of legal prohibition does not automatically produce effective protection when social norms continue to prioritize family reputation, marital continuity, and social harmony over victims' safety. The article contributes to the literature by conceptualizing legal intervention as a process that must operate beyond criminal prosecution, incorporating victim-centered protection, community transformation, institutional responsiveness, and preventive legal education. It proposes a more socially embedded model of intervention capable of challenging the normalization of domestic violence while strengthening victims' autonomy and access to justice.